Pengaruh Likuditas, Total Asset Turnover, Thin Capitalization dan Profitabilias Terhadap Agresivitas Pajak pada Perusahaan Sub Sektor Logam dan Sejenisnya - Sabastian Saka Putra; Wahyumi Ekawanti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The research examines the influence of liquidity, total asset turnover, thin capitalization, and profitability on tax aggressiveness in metal and similar sub-sector companies. The population in this research is metals and similar sub-sector companies listed on the Indonesia Stock Exchange in financial reports for the 2019-2023 period. The sampling technique in this research used a purposive sampling method and a sample of 15 companies was obtained. The analysis technique used is multiple linear regression analysis using SPSS version 26.0 software. The research results show that liquidity and thin capitalization do not have a significant effect on tax aggressiveness, while total asset turnover and profitability have a positive and significant effect on tax aggressiveness.